Peningkatan Kemampuan Mengenal Lima Huruf Vokal Melalui Media Bola Huruf Pada Anak Usia 3-4 Tahun - Siti Karoma (JECED : Journal of Early Childhood Education and Development, 2019)
This research is motivated by the difficulty of children aged 3-4 years in recognizing five vowels that is often children fnd it difficult to mention and distinguish vowels such as the letter â€œeâ€, â€œuâ€ and â€œoâ€. While the letters that are always emembered by children are the letters â€œiâ€ and the letter â€œaâ€. This study aims to describe the learning process by using letter ball media in order to improve the ability to recognize five vowels in children aged 3-4 years and to find out the increased ability to recognize five vowel letters the use of lette ball media in children aged 3-4 years. The method used in this research is classroom action research. This research consisted of pre cycle, cycle I, cyle II, cyle III. Data collection techniques in this study used observation, interviews, non-test assessment, and documentation. The analysis technique in this study uses quantitative descriptive analysis, the results of this study are the se of letter ball media developed very well in cycle III by using letter ball media plus media decorating plastic cups.